The Role of Viral Marketing, Brand Image and Brand Awareness on Purchasing Decisions - Aqila Praditya, Rayyan; Purwanto, Agus (PROFESOR : Professional Education Studies and Operations Research, 2024)
This research aims to examine how brand image, brand awareness, and viral marketing impact the purchasing  decisions. This research is quantitative research conducted on consumers. Sample this research consisted of 543 respondents who were determined using the purposive sampling method. Data collection in this research used a questionnaire instrument distributed via Google Forms. The data analysis technique uses path analysis with the partial least squares structural equation modeling (PLS-SEM) method with data processing tools using Smart-PLS 3.0 software. Questionnaire is closely designed, except for the questions/statements concerning the respondent’s identity, which is a semi-opened questionnaire. Every closed questions/statement, five answer options is given in Likert scale, which consist of: strongly agree (SA) with 5 scores, agree (A) with 4 scores, Neutral (N) with 3 scores, disagree (DA) with 2 scores, and strongly disagree (SDA) with 1 score. The method in data processing is by using PLS and SmartPLS 3.0 software as the tool. The conclusion of this reserach is Viral Marketing have a positive effect and significant to Purchasing Decisions,Brand Image  have a positive effect and significant to Purchasing Decisions. Brand Awareness have a positive effect and significant to Purchasing Decisions.